Pemberdayaan Kolaboratif dalam Penggunaan Limbah Jamu menjadi Pupuk Organik Cair Berkelanjutan (POC) di Desa Wisata Jamu Gendong, Kota Semarang - Nur Muttaqien Zuhri; Nurcahyono Nurcahyono; Wahyu Ida Safira (Lembaga Pengembangan Kinerja Dosen, 2026)
Waste is a major environmental problem that requires careful management. One of the largest sources of waste in cities is households. The use of fresh herbal medicine residue is emphasized in the processing of organic waste from traditional herbal medicine. To produce liquid organic fertilizer (POC), herbal medicine waste is processed and fermented using techniques such as soluble bioactivators. By providing knowledge and techniques for processing household organic waste that can be used as fertilizer for plants in yards, this program aims to improve the community's capabilities. This activity took place from September to November 2025 in Kampung Jamu Gendong Sumbersari, located in Wonolopo Village, Mijen District, Semarang City, Central Java. The activity was carried out through POC training and practice, partner supervision, and activity evaluation. The Sumbersari Jamu Gendong Crafters Group, consisting of 58 people, was the target partner. Using the EM4 liquid fermentation method, herbal medicine waste can be processed into liquid organic fertilizer (POC). The results of the implementation show high enthusiasm among partners and increased community understanding of the processing and utilization of herbal medicine production waste, as well as its independent implementation in the community. This demonstrates better crop yields when POC is used as fertilizer for plants in home gardens.